Kebebasan dan Tanggung Jawab dalam Bumi Manusia - M. Samsul Ma'arif; Diah Dwi Ikranegara (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2025)
Abstract: Freedom and Responsibility in Human Earth. Human Earth is a very popular read and has been translated into various foreign languages. However, Earth of Mankind was once banned from publication, because it was considered to contain propaganda for Communist teachings, Marxism-Leninism. This teaching is dangerous because it contradicts the Pancasila ideology This study aims to reveal how the messages in Earth of Mankind relate to freedom and responsibility. This research uses an objective hermeneutic method as an interpretative approach so that this study can objectively reveal the messages of Human Earth. The results of the study reveal that the Human Earth message adds insight into life in reality. Freedom and responsibility must be owned by both parties and the two must work in balance. Like a "dagger" freedom becomes a sharp weapon, a guardian of self-esteem, a provision for solving problems, but it can become a deadly weapon, an introduction to self-death if it is not balanced with the ability to be responsible.Keywords: Human Earth, Freedom, and Responsibility. Abstrak: Kebebasan dan Tanggung Jawab dalam Bumi Manusia. Bumi manusia merupakan bacaan yang sangat diminati dan sudah dialih bahasakan ke dalam berbagai bahasa asing. Namun Bumi Manusia pernah dilarang terbit, karena dianggap berisi propaganda ajaran Komunis, Marxisme-Leninisme. Ajaran ini berbahaya karena bertentangan dengan ideologi Pancasila. Kajian ini bertujuan mengungkap bagaimana pesan-pesan dalam Bumi Manusia terkait kebebasan dan tanggung jawab. Penelitian ini menggunakan metode objektif hermeneutik sebagai pendekatan interpretatif agar kajian ini dapat mengungkap secara objektif pesan-pesan Bumi Manusia. Hasil kajian mengungkap bahwa pesan Bumi Manusia menambah wawasan hidup dalam kenyataan. Kebebasan dan Tanggung Jawab harus dimiliki oleh seserong dan keduanya harus berjalan seimbang. Ibarat “sebilah belati” kebebasan menjadi senjata tajam, penjaga harga diri, bekal menyelesaikan masalah, tetapi  bisa menjadi senjata mematikan, pengantar kematian diri jika tidak diimbangi dengan kemampuan bertanggung jawab.. Kata kunci: Bumi Manusia, Kebebasan, dan Tanggung Jawab.